CO free esterifications of (Hetero)arenes via transition-metal-catalyzed chelation-induced C–H activation: Recent updates. (8th January 2022) - Joshi, Asha; Singh, Sandeep; Iqbal, Zafar; De, Saroj Ranjan
Abstract: Esters are substantial compounds generally found in the area of pharmaceuticals, agrochemicals, drugs, materials etc., and have been utilized for the formation of many add-value compounds. They are also significant structural blocks in different chemical transformations. Thus, highly efficient transition-metal-catalyzed C–H alkoxycarbonylation of (hetero)arenes offers to achieve important skeleton in a single step in contrast to the other conventional strategies using toxic carbon monoxide (CO). This review provides an overview of this emerging field by highlighting all the chelation-induced esters synthesized till date without the involvement of toxic carbon monoxide (CO). The article has been classified according to the sources of esterification agents along with their reaction methodologies, examples, reaction mechanisms, and synthetic applications. Graphical abstract: Transition-metal-catalyzed C–H alkoxycarbonylation of (hetero)arenes through chelation has drawn considerable attention in the last one decade because of the significant importance of (hetero)aryl esters in the area of pharmaceuticals, agrochemicals, drugs, materials etc. This review highlights the synthetic potential of diverse alkoxycarbonyl surrogates in chelation-induced C–H esterification of (hetero)arenes without involvement of toxic carbon monoxide (CO). Image 1